O terno dos temerosos: as transformações e sentidos de suas práticas culturais na segunda metade do século XX - Silva, Johnisson Xavier (2014)
This research is aimed to study the transformation of cultural meanings and practices of devotion and present in the history of Terno dos Temerosos of the second half of the twentieth century in Januária-MG. Objective by analyzing the symbols, representations, songs, gestures and performances to learn aspects of life, memory, work and social and political demands januarense man. Analyzes the bricolage of cultural practices, statements and inventions of identities through the Terno. Through of the group also studies the formation and social dynamics of coastal communities.